2010
DOI: 10.1037/a0015875
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture with rapidly changing attentional control settings.

Abstract: The classic theory of spatial attention hypothesized 2 modes, voluntary and involuntary. Folk, Remington, and Johnston (1992) reported that even involuntary attention capture by stimuli requires a match between stimulus properties and what the observer is looking for. This surprising conclusion has been confirmed by many subsequent studies. In these studies, however, the observer typically looks for the same property throughout an entire session. Real-world behavior, in contrast, often requires frequent shifts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
88
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 53 publications
7
88
7
Order By: Relevance
“…This result strongly suggests that high-value distractors draw spatial attention, and the subsequent act of disengagement leaves an inhibitory trace at that location (33). Furthermore, a control experiment showed that the effect could only be attributable to reward feedback during training, ruling out the persistence of a deliberate attentional strategy as an explanation; this confirms a recent report that top-down goals in visual search can be adjusted flexibly within seconds (39), and further distinguishes value-driven capture from goal-directed attentional deployment.…”
Section: Discussionsupporting
confidence: 74%
“…This result strongly suggests that high-value distractors draw spatial attention, and the subsequent act of disengagement leaves an inhibitory trace at that location (33). Furthermore, a control experiment showed that the effect could only be attributable to reward feedback during training, ruling out the persistence of a deliberate attentional strategy as an explanation; this confirms a recent report that top-down goals in visual search can be adjusted flexibly within seconds (39), and further distinguishes value-driven capture from goal-directed attentional deployment.…”
Section: Discussionsupporting
confidence: 74%
“…First, the target was defined as a feature singleton in their experiments, leaving open the possibility that participants adopted singleton detection mode as a strategy for identifying the target. In support of this, Lien, Ruthruff, and Johnston (2010) showed that when the target can be identified only on the basis of a particular feature, trial-by-trial adjustments in attentional control settings do, in fact, determine the selectivity in attentional selection. Second, the influence of top-down attentional control settings is still evident even when the cue does not match the target on the previous trial, although contingent capture effects are indeed stronger when the cue matches the former target color (Folk & Remington, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…'R' for red and parity judgment). Lien et al (2010) found that an irrelevant stimulus presented shortly before stimulus onset captured attention only when its color was task-relevant, and that this contingent capture effect was uninfluenced by task switch/repeat, suggesting that task-set preparation during the interval was completely effective in reconfiguring the feature set and thus suppressing capture by the irrelevant color. Experiments in our lab (Longman, Lavric & Monsell, 2013;Longman, Lavric, Munteanu, & Monsell, 2014) have led to a different conclusion for spatial attention.…”
Section: Other Evidence For Attentional Inertiamentioning
confidence: 96%